Macroeconomic and institutional factors on corporate financial flexibility: evidence from sri lanka - Wijerathna, A.G.H.S.K.; Anuradha, P.A.N.S. (University of Jaffna, 2022)
Purpose: Corporate financial flexibility is the capability of a business organization to grab unexpected business opportunities, meet unexpected expenses and raise finance at low cost. Many factors affecting corporate financial flexibility have been discovered in empirical literature, mainly in developed economies. The primary goal of this study is to test the impact of institutional and macroeconomic factors on corporate financial flexibility in Sri Lanka, a developing country context. Methodology:The population of this study is, all the companies listed in Colombo Stock Exchange except companies in banking, finance and insurance industries as they are different from non-financial companies in various aspects. The sample includes 174 firms listed in the Colombo Stock Exchange. Data was collected over the seven years period starting from 2014 to 2020. Data was collected employing secondary sources. Findings: As per the panel regression analysis, both institutional and macroeconomic factors have a significant impact on corporate financial flexibility. Further, the institutional factor profitability has a significant positive impact on corporate financial flexibility. Gross domestic production growth rate has a significant negative impact on corporate financial flexibility and banking sector development has a significant positive impact on corporate financial flexibility. Research Limitations: This study has a sample limitation as the sample excludes the companies in banking, finance and insurance industries. As the study has been conducted in the context of Sri Lanka, the Findings cannot be generalized to developed economies without studying the applicability of the findings at minimum to the countries in the South Asian Region. Implications: Findings would benefit the corporate managers by enabling them to better manage corporate financial flexibility through identification of institutional and macroeconomic factors affecting corporate financial flexibility. Macroeconomic factors in particular are not within the control of business firms. Hence, identifying macroeconomic factors affecting corporate financial flexibility allows corporate decision makers to build appropriate strategies to gain maximum advantage or overcome hurdles posed by them, allowing them to maximize the use of available funds. Future studies in corporate financial flexibility can be extended to test the moderating effect of corporate governance over the relationship between corporate financial flexibility and factors affecting corporate financial flexibility.
Keywords: Colombo stock exchange; Corporate financial flexibility; Institutional factors; Macroeconomics factors; Sri Lanka